Wali Nikah dan Kebebasan Perempuan: Studi Komparatif Hukum Keluarga Malaysia, Maroko, Tunisia dan Syiria - Miftahul Huda (Justicia Islamica, 2004)
This study aims to compare the concept of guardian and women's freedom in family law in Malaysia, Morocco, Tunisia, and Syria. The method used is normative juridical research with a comparative law approach through the analysis of marriage laws in the four countries. The results show that Malaysia and Syria still maintain the obligation of a guardian for women, with certain limitations in granting permission. Meanwhile, Morocco provides flexibility by allowing adult women to marry without a guardian, while Tunisia completely abolishes the role of the marriage guardian as a condition of marriage. These differences reflect variations in the interpretation of Islamic law and state policies on women's rights in marriage. This study emphasizes that women's freedom to choose a spouse must maintain a balance between the principles of Islamic law and human rights.